The Development of Educational Accountability in China and Denmark - Palle Rasmussen; Yihuan Zou (Arizona State University, 2014)
In recent decades, the concept of accountability has attracted more and more attention in public governance and management. The management of education is no exception. This article presents and discusses the evolution and current status of educational accountability in two different national contexts, China and Denmark. Two main sectors of education are covered, general school education and higher education. It is shown that both countries are marked by an increasing concern with educational accountability, that differences in history and culture between the two countries are reflected in the approaches to accountability, but that there are still considerable similarities in the types of accountability pursued. Under the influence of a transnational regime of policy development both countries seem to be moving towards output-based accountability, but more traditional inspection continues to have a role.